Technology for Patient’s Fall Detection System in Hospital Settings: A Systematic Literature Review - Aziz Putra Adhitama; Nurfika Asmaningrum; Dicky Endrian Kurniawan; Anisah Ardiana; Alfid Tri Afandi; Dodi Wijaya; Kholid Rosyidi Muhammad Nur (Health and Technology Journal (HTechJ), 2023)
The prevalence of falls among patients in hospitals around the world is still relatively high. Technology is needed to detect the incidence of patients falling in hospitals. The aim of this study is to analyze technology to detect patient fall in hospital settings. A systematic literature review was chosen as the research design. The databases used to search for literature include Google Scholar, Science Direct, PubMed, and Springer using keywords combined with Boolean operators. The selection of articles is based on several criteria including the publication year 2017-2021, full-text articles, the research setting in a hospital, articles in English, and articles that used research design qualitative, quantitative, and mix-method. The Articles found according to the criteria were 13 articles. The findings showed that there are two types of technology found in this review which are wearable devices and ambient sensor devices. Most of the technical procedure is by connecting the technologies with a wireless network and uploading the data to the server and only a few technologies measure directly. This review also found the advantages and disadvantages of these two types of technology. The health service provider can choose technology by considering the results of the analysis that has been carried out by considering the type of technologies, working procedures, advantages, and disadvantages of the technology so the health service provider can choose the appropriate technology in the hospital.